Moodle as a tool to enhace and improve collaboration students Ama Telidji different departments - Benbertal, Aicha; Makhloufi, Fatima; Charfaoui ,Samia (Faculty of Letters and Foreign Languages Department of English, 2017)
This work is part of a broader project that investigates the impact of the use of Moodle as a pedagogical platform on collaborative learning (Teacher-Students). In order to highlight the attitudes and behavior of teachers towards the use of information and communication technology in higher education, we conducted a survey that was administered to a few teachers working in the field of ICT (Information Communication Technology). The survey was carried out by means of a questionnaire with a sample of fifteen teachers belonging to various departments of the faculties of Laghouat University during the 2016-2017 academic year. The questionnaire includes open-ended as well as closed-ended questions. The work has a descriptive nature; the results obtained in this study revealed that the majority of the teachers investigated have a very positive attitude towards the use of the Moodle pedagogical platform provided that better technical and techno-pedagogical support and training on the computerbased teaching tool will be adapted to the learners’ needs. Besides, the results are in favor of promoting the updating of teaching methods, use of very adequate teaching resources, rapid dissemination of teaching evaluations and facilitating the organization of students' working time. It is important to emphasize that the reluctance observed in the pedagogical use of the computing tool is related more to problems of a technical or temporal nature.